2014
DOI: 10.1371/journal.pone.0099958
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Ischemia Triggers a Transcriptional Response to Down-Regulate Synaptic Proteins in Hippocampal Neurons

Abstract: Transient global cerebral ischemia induces profound changes in the transcriptome of brain cells, which is partially associated with the induction or repression of genes that influence the ischemic response. However, the mechanisms responsible for the selective vulnerability of hippocampal neurons to global ischemia remain to be clarified. To identify molecular changes elicited by ischemic insults, we subjected hippocampal primary cultures to oxygen-glucose deprivation (OGD), an in vitro model for global ischem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 78 publications
4
15
0
Order By: Relevance
“…() and Fernandes et al . (). These two studies found no change in total GluA2 protein abundance at various time points up to 24 h post‐OGD.…”
Section: Discussionmentioning
confidence: 97%
“…() and Fernandes et al . (). These two studies found no change in total GluA2 protein abundance at various time points up to 24 h post‐OGD.…”
Section: Discussionmentioning
confidence: 97%
“…The GluN1 subunit is expressed ubiquitously in the central nervous system (CNS) whereas the GluN2/3 subunits have cell-type and development- specific expression patterns [24]. Recombinant receptors expressed in heterologous cells showed that molecularly defined NMDA receptor isoforms have distinctive functional properties [5, 25]; therefore, regulated subunit expression represents a major mechanism for adjusting the amplitude and time course of NMDA receptor responses during development, following activity- dependent synaptic plasticity, and in certain acute and chronic disorders [7, 9, 10, 13, 2628]. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, ischemia-induced hypoglycemia results in stimulation of AMP-activated protein kinase (AMPK), a stress sensor which induces catabolic pathways and down-regulates anabolic processes such as fatty acid oxidation, glucose uptake and glycolysis upon cellular energy insufficiency [ 4 , 5 ]. Moderate periods of hypoxia and nutrient deprivation provoke a predominant global repression of transcription [ 6 , 7 ], although activation of hypoxia and/or hypoglycemic responsive genes does occur within this general transcriptionally repressive environment [ 8 ]. The transcriptional competence of DNA in eukaryotic cells is determined by its organization in chromatin.…”
Section: Introductionmentioning
confidence: 99%